2016
DOI: 10.1002/aic.15594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small amount of water on the dynamics properties and microstructures of ionic liquids

Abstract: A series of systems of 1‐butyl‐3‐methylimidazolium acetate ([Bmim][Ac]), 1‐butyl‐3‐methylimidazolium tetrafluoroborate ([Bmim][BF4]), and 1‐butyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide ([Bmim][Tf2N]) with a small amount of water were simulated. Viscosities of systems were obtained by nonequilibrium molecule dynamics simulation and the results show that the viscosities change in different ways: for [Bmim][BF4] and [Bmim][Tf2N], viscosities decrease rapidly in the first stage, and then decrease sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 60 publications
3
45
0
Order By: Relevance
“…(d) The experimental and simulated viscosities of the IL–water mixture, where the top panel is BmimAc and the bottom panel is BmimBF 4 . Reproduced with permission from ref ( 102 ). Copyright 2017 Wiley.…”
Section: Z-bonds In Ionic Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…(d) The experimental and simulated viscosities of the IL–water mixture, where the top panel is BmimAc and the bottom panel is BmimBF 4 . Reproduced with permission from ref ( 102 ). Copyright 2017 Wiley.…”
Section: Z-bonds In Ionic Liquidsmentioning
confidence: 99%
“…However, our previous work has indicated that a small amount of water can unexpectedly increase the viscosity of Bmim acetate ( Figure 6 d). 102 The abnormal increase in the viscosity is attributable to a chainlike anion···water···anion cluster structure, where the chain length of the cluster increases with the IL concentration when the water content is less than 2%. The chainlike cluster does not disrupt the Z-bond within the ILs and can enhance the diffusive resistance, leading to a substantial increase in the viscosity.…”
Section: Z-bonds In Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of interactions, there is a hydrogen bond (HB) weakening between ion pairs but However, there are some exceptions and [C 4 mim][Ac] viscosity shows a water content viscosity dependency. Initially, a small water amount (up to 0.02 wt%) induces an increase in the viscosity, which decreases with the increase in water addition [128]. By MD simulations, the authors attributed this anomalous behaviour to a water-induced structural change in the IL, with the formation of chain-like {anion•••water•••anion•••}n structure, which length increases with the water content up to 0.02 wt%.…”
Section: Water Effectmentioning
confidence: 99%
“…Besides, ILs are also mixed with other molecular solvents to tune their properties and/or reduce costs [5] . It has been reported that a trace amount of water can dramatically alter the viscosity, resulting in significant changes in physicochemical properties [6] . Wang et al.…”
Section: Introductionmentioning
confidence: 99%